2009
DOI: 10.1111/j.1365-2141.2009.07794.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased erythropoiesis of β‐thalassaemia/Hb E proerythroblasts is mediated by high basal levels of ERK1/2 activation

Abstract: Increased erythropoiesis of b-thalassaemia/Hb E proerythroblasts is mediated by high basal levels of ERK1/2 activationThe thalassaemias are a group of disorders characterized by the under production of globin chains as a consequence of a wide range of underlying genetic abnormalities (Weatherall & Clegg, 2001). The a and b chains of haemoglobin A are the most commonly affected genes and both a-and b-thalassaemias represent a worldwide clinical problem (Weatherall & Clegg, 2001). The underproduction of one chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 57 publications
(73 reference statements)
7
24
1
Order By: Relevance
“…The role of cAMP in HSC specification has recently been reported by Diaz et al [20], and increased cAMP has been shown to drive erythroid proliferation [21]. TNFα is a recognized inhibitor of hematopoietic progenitor development and of erythropoiesis [22].…”
Section: Resultsmentioning
confidence: 99%
“…The role of cAMP in HSC specification has recently been reported by Diaz et al [20], and increased cAMP has been shown to drive erythroid proliferation [21]. TNFα is a recognized inhibitor of hematopoietic progenitor development and of erythropoiesis [22].…”
Section: Resultsmentioning
confidence: 99%
“…Under these growth conditions more than 95% of cells show erythroblast morphology as established previously (Wannatung et al, 2009). Cell numbers were established by trypan blue exclusion assay and counting using a cell counting chamber.…”
Section: Sample Collection and Erythroid Cell Culturementioning
confidence: 99%
“…CD34 þ hematopoietic stem cells (HSCs) were isolated from peripheral blood samples and cultured under conditions that produced differentiation in the erythroid lineage as described in previously (Lithanatudom et al, 2010;Wannatung et al, 2009) and see more detail in Supplemental materials and methods. Under these growth conditions more than 95% of cells show erythroblast morphology as established previously (Wannatung et al, 2009).…”
Section: Sample Collection and Erythroid Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…58 And in b-thalassemia proerythroblasts, phospho-C-Raf levels correlate with increased ERK activation. 59 Mek2 is dispensable for mouse development, 60 implicating prime roles for Mek1 in Erk1/2 signaling. In mice expressing a truncated EpoR-HM allele, pharmacologic inhibition of Mek reverses stage-specific EPC differentiation defects, 61 whereas in mice with somatic inactivation of Nf1, Mek1/2 inhibition decreases splenomegaly and enhances erythropoiesis.…”
Section: Epor Signal Transduction Via Rat Sarcoma/ Mek Kinase/mitogenmentioning
confidence: 99%